Fig. 3 in First three-dimensional skull of the Middle Triassic mixosaurid ichthyosaur Phalarodon fraasi from Svalbard, Norway - Roberts, Aubrey Jane; Engelschiøn, Victoria Sjøholt; Hurum, Jørn Harald (Zenodo, 2022)
Fig. 3. The computed tomography rendered segmentation of rostral elements of mixosaurid ichthyosaur Phalarodon fraasi (Merriam, 1910) PMO 235.393, from the Botneheia Formation, Middle Triassic of the Isfjorden area in Spitsbergen, Svalbard. Right dentary and maxilla in lingual (A1) and labial (A2) views, right dentary (A3) in dorsal view, right maxilla in dorsal (A4) and lateral (A5) views. Note that the dorsal extent of the maxilla is not complete. Scale bars 10 mm. Published as part of Roberts, Aubrey Jane, Engelschiøn, Victoria Sjøholt & Hurum, Jørn Harald, 2022, First three-dimensional skull of the Middle Triassic mixosaurid ichthyosaur Phalarodon fraasi from Svalbard, Norway, pp. 51-62 in Acta Palaeontologica Polonica 67 (1) on page 56, DOI:10.4202/app.00915.2021, http://zenodo.org/record/10981077